Factors associated with racing performance and career duration for Victorian‐born Thoroughbreds. Issue 1 (14th October 2021) - Flash, ML; Crabb, HK; Hitchens, PL; Firestone, SM; Stevenson, MA; Gilkerson, JR
Abstract : The number of horses leaving the Australian Thoroughbred (TB) racing industry each year is of concern to animal welfare advocates, public and regulators. A horse's previous athletic performance is a significant driver of retirement from racing. Racehorse performance can be measured in terms of the total number of starts, duration of racing and prize money earned. This study investigated Australian racing records for the 2005 and 2010 Victorian TB foal crops to identify factors associated with total number of starts, racing career duration, prize money earned and age of last race start‐up to the 10‐year‐old racing season. Racing Australia registered 4, 577 TB horses born in Victoria in 2005 (n = 2, 506) and 2010 (n = 2, 071) that raced in Australia. Horses that started racing at 2‐years of age had fewer race starts in their first racing season but an increased total number of starts, prize money and duration of racing. The median age of last start (LS) was five (Q1 4; Q3 7) years. Horses that had won a race, had a maximum handicap rating of 61 or above and those racing over distances of more than 2, 400 m had an increased racing career duration and an age of last race start greater than 6‐years of age. Horses participating in jumps races (n = 63) had the longest careers and older age of LS. These horses were more likely to have had a handicap rating over 80 and were just as likely to start their racing careers as 2‐years‐olds.